Interpellation and Urban transformation: Lisbon's sardine subjects - Davies, Archie; Brooks, Andrew (Social & cultural geography, 2021)
Many cities have tried to reinvent themselves, but what role can new material and symbolic traditions play in urban transformations? Here we interrogate how ideology can be spread through a new tactile motif. Geographical work has focused on state-led, event and architecture-based development projects that drive change in the city. We suggest that the aesthetic, the sensory and the behavioural can also be fields through which urban change is driven. In Lisbon the sardine has emerged as a moniker for the city. An informal coalition of state and non-state interests have deployed the sardine to interpellate urban subjectivity, effecting processes of consumption and specifically touristification in the city. Building on the idea of interpellation we argue that both sardine symbols and actual sardines have hailed subjects in the city and the behaviours of residents and tourists have modified in response. Although the sardine is not the prime mover in urban transformation, our fieldwork shows how the affects of a new icon produce effects through invented traditions, street festivals and the tourist economy.